Multispectroscopic and molecular modeling strategy to explore the interaction of cholest-5-en-7-one with human serum albumin: DFT and Hirshfeld surface analysis - Mahboob Alam (Elsevier, 2021)
The present study accounts for cholest-5-en-7-one (steroid) synthesis using selenium dioxide and silica as well as its identification using high-resolution mass spectrometry (HRMS), FT-IR, NMR, and elemental analysis. Density functional theory (DFT) calculations were used to optimize the steroid's geometry, which was then compared to single-crystal X-ray diffraction data, indicating that the computational and experimental results were in good agreement. UV–vis absorption titration, fluorescence spectral methods, circular dichroism (CD), and dynamic light scattering (DLS) were used to investigate the well-identified steroid's in vitro molecular interaction with human serum albumin (HSA). The results and binding parameter indicate that the steroid has significant binding affinity for HSA. Molecular docking was performed and found that the steroid can interact with the hydrophobic cavity of HSA through hydrogen and hydrophobic contacts. Molecular dynamics simulation was used to confirm the stability of the HSA-steroid complex. Combined quantum mechanics-molecular mechanics (QM-MM) methods were applied to know binding energy of system and individual components for atomic level interactions indicating a significant interaction between the steroid and the biomacromolecules. The findings presented here contribute to a better understanding of steroid pharmacodynamics.